Globally defined Carroll symmetry of gravitational waves - Elbistan, M.; Zhang, P. M.; Horvathy, P. A. (Elsevier, 2026)
The local Carroll symmetry of a gravitational wave found in Baldwin-Jeffery-Rosen coordinates is extended to a globally defined one by switching to Brinkmann coordinates. Two independent globally defined solutions of a Sturm-Liouville equation allow us to describe both the symmetries (translations and Carroll boosts) and the geodesic motions. One of them satisfies particular initial conditions which imply zero initial momentum, while the other does not. Pure displacement arises when the latter is turned off by requiring the momentum to vanish and when the wave parameters take, in addition, some particular values which correspond to having an integer half-wave number. The relation to the Schwarzian derivative is highlighted. We illustrate our general statements by the P & ouml;schl-Teller profile.
Keywords: Carroll Symmetry; Displacement Memory Effect; Gravitational Waves